2002
DOI: 10.1124/jpet.300.3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Inhibits theN-Methyl-d-Aspartate Receptor-Mediated Responses by Directly Interacting with The Receptor/Channel Complex

Abstract: Amphetamine (AMPH) induces behavioral sensitization and neurotoxicity primarily by enhancing the dopamine-mediated neurotransmission. However, the involvement of the N-methyl-D-aspartate (NMDA) receptor in AMPH-induced neuropathology is also known. Recent investigation has found that high concentration of dopamine could inhibit NMDA receptor-mediated responses by blocking the NMDA receptor channel. 3 H]TCP binding suggested that the high-potency inhibition was produced by decreasing agonist-induced activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Short-term, repeated administration of METH to rodents has been shown to increase hippocampal and striatal glutamate content (Mark et al 2007;Rocher and Gardier, 2001) while long-term METH administration was shown to deplete hippocampal glutamate content (Kaiya et al 1982). Amphetamines have been shown to displace [ 3 H]N-[1-(2-thienyl)cyclohexyl] piperidine (TCP) binding to the NMDA receptor ion channel, in addition to, decreasing NMDA-induced intracellular 45 Ca accumulation in rat cortical neurons (Yeh et al, 2002). A recent report similarly demonstrated that short-term METH (≥1.0 μM) exposure antagonizes NMDAinduced neurotoxicity in organotypic hippocampal slice cultures, suggesting direct or indirect modulation of NMDA receptor activity (Smith et al, 2007).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Short-term, repeated administration of METH to rodents has been shown to increase hippocampal and striatal glutamate content (Mark et al 2007;Rocher and Gardier, 2001) while long-term METH administration was shown to deplete hippocampal glutamate content (Kaiya et al 1982). Amphetamines have been shown to displace [ 3 H]N-[1-(2-thienyl)cyclohexyl] piperidine (TCP) binding to the NMDA receptor ion channel, in addition to, decreasing NMDA-induced intracellular 45 Ca accumulation in rat cortical neurons (Yeh et al, 2002). A recent report similarly demonstrated that short-term METH (≥1.0 μM) exposure antagonizes NMDAinduced neurotoxicity in organotypic hippocampal slice cultures, suggesting direct or indirect modulation of NMDA receptor activity (Smith et al, 2007).…”
Section: Introductionmentioning
confidence: 69%
“…Furthermore, some studies suggest that METH may act as an NMDA receptor antagonist (Smith et al, 2007;Yeh et al, 2002). Yeh et al (2002) reported that METH reduced NMDAinduced intracellular Ca 2+ accumulation as well as displaced [H 3 ]TCP binding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations